Valčík na rozloučenou : román - Kundera, Milan; Pochoda, Elisabeth (Brno : Atlantis, 2011)
Rafinovaně komponovaný román fraškovitého nadhledu.
Poznámka autora
Keywords: češka književnost - proza - roman - 20. st